2016
DOI: 10.1186/s12968-017-0358-2
|View full text |Cite
|
Sign up to set email alerts
|

Local coronary wall eccentricity and endothelial function are closely related in patients with atherosclerotic coronary artery disease

Abstract: BackgroundCoronary endothelial function (CEF) in patients with coronary artery disease (CAD) varies among coronary segments in a given patient. Because both coronary vessel wall eccentricity and coronary endothelial dysfunction are predictors of adverse outcomes, we hypothesized that local coronary endothelial dysfunction is associated with local coronary artery eccentricity.MethodsWe used 3 T coronary CMR to measure CEF as changes in coronary cross-sectional area (CSA) and coronary blood flow (CBF) during iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Endothelial-dependent coronary artery vasoreactivity is a significant indicator of vascular function [6,7]. Endothelial dysfunction is characterized by decreased nitric DOI: 10.1159/000489958 oxide (NO) bioavailability and predicts late cardiovascular events [8].…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial-dependent coronary artery vasoreactivity is a significant indicator of vascular function [6,7]. Endothelial dysfunction is characterized by decreased nitric DOI: 10.1159/000489958 oxide (NO) bioavailability and predicts late cardiovascular events [8].…”
Section: Introductionmentioning
confidence: 99%
“…Area measurement precision and accuracy can be further improved with smaller acquisition voxels as long as the SNR remains above 30. Importantly, the currently used CEF‐MRI protocol distinguishes area changes of 4‐5% at SNR levels achieved in vivo. Noninvasive CEF measures by MRI promise a window into predicting atherosclerotic progression and testing new interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have shown isometric handgrip exercise induced mean coronary cross‐sectional area changes from 10–20% in healthy vessels and reduced dilation or even a paradoxical constriction from 2 to −12% in diseased vessels, approximately a 20% absolute difference in area change on average between healthy and diseased vessels. The ability to measure one‐fifth or a quarter of the difference between healthy and diseased enables the comparison of patient groups at earlier stages of atherosclerotic disease progression and the investigation of the impact of medical or lifestyle interventions on CEF where the improvement may only be a fraction of the difference measured between healthy and diseased vessels.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations